KEANEKARAGAMAN JENIS POHON DI REPONG DAMAR PESISIR TENGAH DAN PESISIR SELATAN - Mefki Sunardi; Afif Bintoro; Rusita Rusita (Lambung Mangkurat University-Indonesia, 2021)
Repong Damar is a form of hereditary since the days of the Dutch colonial government owned by the Krui Lampung people in the West Coast. Repong damar functions as a buffer zone in the Bukit Barisan Selatan National Park. The flagship product from Non-Timber Forest Products (NTFPs) in Indonesia found in Krui Pesisir Barat is Damar Mata cat (Shorea javanica). The management and use of resin repong can cause various types of plants. Damar reong found in the Regency of Pesisir Barat has very important benefits for life, and therefore it is necessary to act as a preservation effort for this repong damar to remain sustainable and continue to grow. One of the efforts made is to analyze the diversity of tree species that are in the resin dunk. This study aims to determine the diversity of tree species in the Central Pongir Pongon Repong Pahmungan and Tenumbang Pekon Coastal Equipment and to compare the diversity of tree species in the Central Pekon Pahmungan and South Pekon Tenumbang Pekon Coastal Areas. This research was conducted in August-September 2019 which is located in two locations, namely Tenumbang Pekon, Pesisir Selatan District and Pahmungan Pahmungan Tengah Pesisir Tengah District, Pesisir Barat District. The method used to determine the diversity of tree species using the plot line method where the determination of the plot starting point is done by Systematic sampling with random sampling. Analysis of the data to be used is the relative density (KR), relative frequency (FR), and relative closure area (CR). Importance Value Index (INP) = KR + FR + CR (Indriyanto, 2006). The Diversity Index used is the Shanon Wiener Diversity Index (H '). The results of the research that have been carried out there are 28 species of trees found in Pahonungan Pahmungan, Central Pesisir Tengah and 32 species found in Tenumbang Pekon, Pesisir Selatan District and Diversity of tree species in Pahonungan Pekm Tengah, Pesisir Tengah District, 1.86 and Diversity of tree species in Pekon Tenumbang. Pesisir Selatan District at 2.44.